Protection of Indonesia’s Genetic Resources and Traditional Knowledge (International and National Legal Perspectives) - Medina, Dayu; Enggriyeni, Dewi (Nagari Law Review, 2025)
Indonesia, with its abundant biodiversity, has important genetic resources (GR) and traditional knowledge (TK) in various fields. A normative juridical approach is used in this study. This research highlights the legal protection of GR and TK to prevent biopiracy by examining the national and international legal frameworks, as well as the challenges faced. International instruments such as the CBD, Nagoya Protocol, and TRIPS, as well as national laws (Law No. 5 of 1990 and Law No. 13 of 2016), have not been fully effective due to mismatches in regulatory objectives and implementation outcomes. Challenges in their implementation require commitment, knowledge, and collaboration of all elements of the nation. Regulations on the utilization of genetic resources and traditional knowledge have been regulated in several international and national legal sources. However, these regulations have not been able to protect the utilization of Indonesia's genetic resources and traditional knowledge from biopiracy and prevent the illegitimate granting of patents. This is because the basis of protection of genetic resources and traditional knowledge at the beginning was more focused on conservation without concerning at private aspects, especially commercialization. Therefore, the separate arrangements are needed in the use of genetic resources and traditional knowledge. In addition, the technical derivative regulations are also needed to address on the root of the problem in protecting Indonesia's genetic resources.